Resistant hypertension and renal sympathetic denervation—what does the future hold?. (December 2014) - Sharma, Prashant; Alraies, M. Chadi
Abstract: Hypertension is a major public health problem and despite adequate pharmacological treatment, blood pressure remains uncontrolled in a subset of patients with hypertension. Renal sympathetic denervation is a percutaneous catheter-based treatment for select patients with resistant hypertension. In this article, we discuss the development of this intervention, its role in patients with resistant hypertension and the need for guarded optimism in the future of device-directed renal sympathetic denervation.